Mechanisms of Resistance To -Lactam Antibiotics in Staphylococcus aureus - Maribel Castellano González; Armindo Perozo Mena (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2010)
S. aureus has shown a great power of adaptation to antimicrobial agents, acquiring, step-by step, resistance to all available antibiotics for treatment of the infections it causes. S. aureus has three major mechanisms of resistance to B-lactam antibiotics: enzyme mediated (penicillinase or B-lactamase) by which the antibiotic is inactivated; intrinsic resistance,which is not due to drug inactivation and accounts for methicillin resistance;and modifications of penicillin-binding proteins (PBPs). Additionally, S. aureus can express the tolerance phenomenon, in which there is a dissociation of the inhibitory and killing actions of â-lactam antibiotics. Of these, the most important mechanism is intrinsic resistance, which is probably more complex because several factors can affect its expression.